Chocolate Cities 2018
DOI: 10.1525/california/9780520292826.003.0012
|View full text |Cite
|
Sign up to set email alerts
|

Mary, Dionne, and Alma

Abstract: The second of three chapters on the power of chocolate cities, this chapter centers the lives, activism, and pioneering efforts of three black women professionals, entertainers, and community activists: Mary Hill Sanders, Dionne Warwick, and Alma Burrell. Exploring their lives, health setbacks, and push against the glass ceiling and racial oppression, the authors highlight their sophisticated and politically informed racial geography of the United States. Detailing the movement of black people throughout the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We can see that the differences in ele v ation between the bandpass calibrators and the target were 14 • , 22 • , and only 2 • on 2015.3, 2016.8, and 2017.9, respectively. Therefore, at least on the last epoch we would not expect to find the contamination related by (Hunter et al 2018 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We can see that the differences in ele v ation between the bandpass calibrators and the target were 14 • , 22 • , and only 2 • on 2015.3, 2016.8, and 2017.9, respectively. Therefore, at least on the last epoch we would not expect to find the contamination related by (Hunter et al 2018 ).…”
Section: Discussionmentioning
confidence: 97%
“…Since many molecules were detected at different wavelengths, it was not surprising that we started to see molecular absorption at ALMA frequencies (Smith, Ginsburg & Bally 2018 ;Bordiu & Rizzo 2019 ;Morris et al 2020 ). Ho we ver, a recent ALMA report (Hunter et al 2018 ) showed that sometimes telluric lines are not entirely remo v ed from the final spectrum, appearing as absorption features. Therefore, some additional analysis is required to recognize if an absorption feature is intrinsic to the source and not an artificial feature due to a calibration problem.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation